1993
DOI: 10.1029/92jd02646
|View full text |Cite
|
Sign up to set email alerts
|

Circulation mechanisms related to northeast Brazil rainfall anomalies

Abstract: This study explores the role of the upper ocean for circulation anomalies in the overlying atmosphere, with focus on the late boreal winter and extreme climatic events in northeast Brazil. Data sources comprise rainfall records in the Nordeste, surface ship observations of the sea surface temperature (SST), pressure, and wind fields (COADS, period 1948-1990), satellite observations of tropical convection (HRC, 1971(HRC, -1988, and upper air analyses of the European Centre for Medium Range Weather Forecasts (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
0
10

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(167 citation statements)
references
References 20 publications
7
148
0
10
Order By: Relevance
“…Moreover, a SST variability mode in the tropical Atlantic displaying an anti-symmetric SST anomaly pattern in relation to the equator has long been related to interannual climate variations over northeastern Brazil (e.g. Hastenrath and Heller, 1977;Weare, 1977;Hastenrath, 1978Hastenrath, , 1990Moura and Shukla, 1981;Hastenrath and Greischar, 1993;Nobre and Shukla, 1996;Souza et al, 2000). Furthermore, positive simultaneous correlations between the SST anomalies in the southwestern subtropical Atlantic and rainfall anomalies over Uruguay and southern Brazil during austral summer have been documented (Diaz et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a SST variability mode in the tropical Atlantic displaying an anti-symmetric SST anomaly pattern in relation to the equator has long been related to interannual climate variations over northeastern Brazil (e.g. Hastenrath and Heller, 1977;Weare, 1977;Hastenrath, 1978Hastenrath, , 1990Moura and Shukla, 1981;Hastenrath and Greischar, 1993;Nobre and Shukla, 1996;Souza et al, 2000). Furthermore, positive simultaneous correlations between the SST anomalies in the southwestern subtropical Atlantic and rainfall anomalies over Uruguay and southern Brazil during austral summer have been documented (Diaz et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past four decades the interhemispheric SST gradient in late boreal winter has been shown [Wagner, 1996] In the long-term mean a near-equatorial band of warmest surface waters is known [Hastenrath and Greischar, 1993] to induce hydrostatically a low-pressure trough, into which the lower tropospheric airstreams from the two hemispheres converge, thus forming the notorious ITCZ with its intense convective activity. The present analysis documented the associated vigorous upward motion feeding the upper tropospheric divergence and showed that the divergent outflow is directed mainly into a band of upper tropospheric convergence and subsidence over the tropical North Atlantic.…”
Section: Trendsmentioning
confidence: 99%
“…An index of March-April rainfall in Brazil's Nordeste (Figures 1 and 2e) was compiled from a network of 27 precipitation gages, as described by Hastenrath [1990] and Hastenrath and Greischar [1993].…”
Section: Data and Analysismentioning
confidence: 99%
“…The most persistent feature related to the rainy season in this region mainly in the northern sector, is the Intertropical Convergence Zone (ITCZ) (e.g. Hastenrath and Heller, 1977;Moura and Shukla, 1981;Hastenrath and Greischar, 1993). Located in the upper branch of the Hadley Cell, the ITCZ is characterized by low surface pressure (the equatorial trough), maximum sea surface temperature (SST), confluence of northern and southern trade winds, maximum convergence and maximum convective cloud cover.…”
Section: Introductionmentioning
confidence: 99%